STUDY OF PATTERN OF SKULL FRACTURE IN VICTIMS OF TWO WHEELERS DUE TO ROAD TRAFFIC ACCIDENTS AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2020)
In an ancient time, people used to have animals for the purpose of transport to reach from one distance to another. It used to be tedious and at the same time tiring also. To overcome this, invented vehicles like bullock cart, bicycle, tricycle, motorcycle, four-wheeler, train etc, to reach his destination very fast. But same time ignored his inner conscience, became the victim of damages of his own invention by means of road traffic accidents. Inspite of huge benefit, vehicle is a common killer of human. Road traffic accidents take major portion of magnitude of mortality in developing and developed countries. Also the major concern of disability. Road traffic accident poses itself as a major epidemiological and legal problem.
Keywords: skull fracture; road traffic accidents; two wheeler accidents